Protocol for preparation of primary alveolar epithelial type I cells from mouse lungs - Lulu Huang; Amy Tang; Bojing Shao (STAR Protocols)
Summary: Currently, the only approach for obtaining alveolar epithelial type I (AT1) cells is through the differentiation of cultured AT2 cells, which has several limitations. Here, we present a protocol to prepare AT1 cells directly from mouse lungs. We detail the steps for dissociating epithelial cells from the alveoli, followed by the purification of AT1 cells. Additionally, we describe how to assess the purity of AT1 cells using immunofluorescence staining and flow cytometry, along with approaches for verifying their functions. : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.